New species of the genus Picobia (Cheyletoidea: Syringophilidae) parasitizing tyrannid birds (Passeriformes: Tyrannidae) - Glowska, Eliza; Milensky, Christopher M. (Zootaxa, 2014)
Three new quill mite species of the genus Picobia Haller (Cheyletoidea: Syringophilidae) are described from 6 host species of the family Tyrannidae (Passeriformes), P. ochoi sp. nov. from Tolmomyias sulphurescens (Spix) (Guyana), P. schmidti sp. nov. from Lophotriccus pileatus (Tschudi) (type host) (Peru) and Hemitriccus margaritaceiventer (Orbigny & Lafresnaye) (Guyana), and P. myiopagi sp. nov. from Myiopagis gaimardii (Orbigny) (type host) (Guyana), M. subplacens (Sclater) (Peru) and Elaenia ruficeps Pelzeln (Guyana).